93.7k views
7 votes
What is -2 1/3 - (-5) =?

What is -2 1/3 - (-5) =?-example-1
User Let
by
5.6k points

1 Answer

10 votes

Answer:


2(2)/(3)

Explanation:

Given the following question:


-2(1)/(3) -(-5)

To find the answer to this question we will use KCF (Keep, Change, Change) because we are subtracting from a negative. Then we find the common denominator and subtract the numerators.


-2(1)/(3) -(-5)

-5=(-5)/(1)

-2(1)/(3) =3*-2=-6+-1=-7=(-7)/(3)

(-7)/(3) -(-5)/(1)

(-7)/(3) *1=(-7)/(3)

(-5)/(1) *3=(-15)/(3)

(-7)/(3) -(-15)/(3)

-7+15=(8)/(3) =8/3=2(2)/(3)

2(2)/(3)

Hope this helps.

User Omar Alvarado
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.